Inhibition of cadmium uptake by wheat with urease-producing bacteria combined with sheep manure under field conditions. (April 2022) - Han, Hui; Wu, Xuejiao; Bolan, Nanthi; Kirkham, M.B.; Yang, Jianjun; Chen, Zhaojin
Abstract: In heavy metal-contaminated farmland, microorganisms or organic fertilizers can be used to minimize heavy metal uptake by crops to ensure food safety. However, the mechanisms by which urease-producing and metal-immobilizing bacteria combined with manure inhibit Cd uptake in wheat ( Triticum aestivum L.) remain unclear. Herein, the effects of Enterobacter bugandensis TJ6, sheep manure (SM), and TJ6 combined with SM on Cd uptake by wheat and the mechanisms involved were investigated under field conditions. The results showed that strain TJ6 increased the urease activity and the proportion of strains with a high Cd adsorption capacity in SM, thereby enhancing the Cd adsorption capacity of SM in solution. Strain TJ6 combined with SM improved the rhizosphere soil urease activity, NH4 + /NO3 − ratio, and pH, thus reducing the Cd content (75.9%) in wheat grain. In addition, TJ6+SM reduced the bacterial community diversity but shifted the structure of the bacterial community in rhizosphere soil. Interestingly, the relative abundances of urease-producing bacteria and metal-immobilizing bacteria ( Enterobacter, Bacillus, Exiguobacterium, Rhizobium, and Serratia ) in rhizosphere soil were enriched, which enhanced wheat resistance to Cd toxicity. These results showed that urease-producing and metal-immobilizing bacteria combined with sheep manure can inhibit the uptake of Cd by wheat. Graphical abstract: Image 1 Highlights: Enterobacter sp . TJ6 combined with manure reduced Cd accumulation in wheat grain. Strain TJ6 increased the proportion of strains with high Cd adsorption capacity in SM. Urease activity and NH4 + /NO3 − ratio in the wheat rhizosphere soil were increased. Heavy metal-immobilizing bacteria in the wheat rhizosphere soil were enriched. TJ6+SM decreased the expression of Cd transporter gene in wheat roots.